Comparison of cold-water immersion vs. Passive recovery on indicators of muscular fatigue in youth handball players during a congested tournament - Braulio Sánchez-Ureña; José A. Ugalde-Ramírez; Randall Gutiérrez-Vargas; José Trejos-Montoya; Jose Pino-Ortega; Juan C. Gutiérrez-Vargas; Daniel Rojas-Valverde (Federación Extremeña de Balonmano; University of Extremadura, 2023)
This study aimed to compare the effectiveness of CWI and passive recovery on indicators of fatigue in handball players after three consecutive days of competition. The study was applied to 41 handball players belonging to 8 handball clubs in Costa Rica (20 men and 21 women; 20.1 ± 4.08 years; weight, 68.03 ± 13.13 kg; VO2max= 42.40 ± 5.31 ml / kg / min). Four teams were selected and randomly assigned one of the two post-game treatments, one group received immersion and another passive rest, it was developed during a handball tournament of three consecutive days on a 20x40m field. Each team played one game per day with two periods of 30 min. No significant differences were found in tensiomyography, CMJ, DOMS, TQR and CK between the treatment group and the recovery group. It is concluded that CWI seems to be more effective than PR in variables such as DOMS and in Recovery Perception and the combination of different recovery methods should be analyzed in future research to better understand which the best strategies are to accelerate recovery of athletes during competitions